2022
DOI: 10.3390/gels8020130
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Properties of Phosphate-Based Geopolymer Synthesized with the Spent Fluid Catalytic-Cracking (SFCC) Catalyst

Abstract: As a common industrial by-product, the spend fluid catalytic-cracking (SFCC) catalyst was used to prepare phosphate-based geopolymer for the first time. The structure and property of geopolymer with phosphoric acid concentration ranging from 6 to 14 mol/L was characterized by compressive strength measurements, X-ray powder diffraction (XRD), Fourier Transform Infrared spectroscopy (FTIR), scanning electron microscopy (SEM), and 27Al and 29Si nuclear magnetic resonance (NMR). A stable binder was formed with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…However, for geopolymer synthesized with SFCC catalyst with increasing acid concentration, the ratio of Al 6 -OP to Al 6 -OSi is 3:1 to 5:1, but for geopolymer prepared with MK, it's close to 2:1. The former has more Al-O-P bonds and Si-O-P bonds, while the latter has more Si-O-Al bonds [72].…”
Section: Natural Pozzolanmentioning
confidence: 97%
See 1 more Smart Citation
“…However, for geopolymer synthesized with SFCC catalyst with increasing acid concentration, the ratio of Al 6 -OP to Al 6 -OSi is 3:1 to 5:1, but for geopolymer prepared with MK, it's close to 2:1. The former has more Al-O-P bonds and Si-O-P bonds, while the latter has more Si-O-Al bonds [72].…”
Section: Natural Pozzolanmentioning
confidence: 97%
“…3.8.6. SFCC SFCC catalyst is an industrial solid waste used to prepare SAPG for the first time [72]. When the PA concentration was 12 M, the geopolymer reached a maximum compressive strength of 30.2 MPa.…”
Section: Natural Pozzolanmentioning
confidence: 99%
“…The compressive strength of geopolymer was found to be between 31 and 41 MPa. However, the authors employed alkali-activation of geopolymers in these investigations, whereas Wan et al (2022) 35 used SFCC catalyst as a raw material for the formation of phosphate geopolymers with a maximum compressive strength of 30.2 MPa.…”
Section: Synthesis and Classificationmentioning
confidence: 99%
“…Wan et al (2022) 35 investigated whether the concentration of phosphoric solutions has a significant effect on the mechanical properties of geopolymer synthesized with the SFCC catalyst using the SFCC catalyst as an aluminosilicate precursor and acid solutions with concentrations of 6, 8, 10, 12, and 14 mol L −1 . When the acid content was between 6 and 12 mol L −1 , a stable binder with a compressive strength ranging from 9.8 to 30.2 MPa was prepared ( Fig.…”
Section: Synthesis and Classificationmentioning
confidence: 99%
“…These materials have been shown to exhibit exceptional tensile strength as a nanocomposite polymer matrix and provide excellent thermal stability at temperatures above 350 °C [ 91 , 96 ]. Previous work has demonstrated that polymer reinforcement of geopolymer materials improves the bulk properties by controlling the microstructure and reducing crack initiation/growth [ 55 , 99 ]. Thus, we hypothesize that the incorporation of PBDT and PBDI will reduce microporosity and serve as reinforcements within the geopolymer particulate and binding phases.…”
Section: Introductionmentioning
confidence: 99%